DEKONSTRUKSI PEMAHAMAN BUDAYA JAWA TENTANG HAKIKAT DAN HUBUNGAN KAWULA-GUSTI PADA LAKON WAYANG ”SEMAR KUNING” - Sindung Tjahyadi (Jurnal Filsafat "WISDOM", 2009)
AbstractIn the Javanese minds, the essence and relationship of manand God are the cornerstone to build a holistic view of genealogy and direction of life. The wayang/ puppet story of “Semar Kuning” is one of some exemplary narrations which comprehends the relation of man-God in common people perspectives in the case that the legitimacy of King-God is questioned metaphysically and ethically.The character of Semar in the Javanese world has a centralsymbolic and mystical role to bring a harmony and overcome adisorder in the natural and social life. The central symbolic role of Semar in protecting and taking care of the world is based onJavanese understanding of the man-God relationship which tends to accept its relationship in ontical sense. Although this tendency is a part of religious perspective mainstream at the time, it still keeps the magi function of the “wayang kulit” performance to overcome cosmic and ethical disharmony in the world. In the ethical terminology, the ethical discourse that had been given in the wayang/ puppet story of “Semar Kuning” is a virtue ethics which shows bad and good moral attitudes.Keyword: Deconstruction, Javanese Perspectives, the man-Godrelationship, Semar Kuning, Wayang/ puppet.